Design of a syringe extension device (Chloe SED®) for low-resource settings in sub-Saharan Africa: a circular economy approach - Samenjo, Karlheinz Tondo; Ramanathan, Aparna; Gwer, Stephen Otieno; Bailey, Robert C.; Otieno, Fredrick Odhiambo; Koksal, Erin; Sprecher, Benjamin; Price, Rebecca Anne; Bakker, Conny; Diehl, Jan Carel (Frontiers in Medical Technology, 2023)
Underfunded healthcare infrastructures in low-resource settings in sub-Saharan Africa have resulted in a lack of medical devices crucial to provide healthcare for all. A representative example of this scenario is medical devices to administer paracervical blocks during gynaecological procedures. Devices needed for this procedure are usually unavailable or expensive. Without these devices, providing paracervical blocks for women in need is impossible resulting in compromising the quality of care for women requiring gynaecological procedures such as loop electrosurgical excision, treatment of miscarriage, or incomplete abortion. In that perspective, interventions that can be integrated into the healthcare system in low-resource settings to provide women needing paracervical blocks remain urgent. Based on a context-specific approach while leveraging circular economy design principles, this research catalogues the development of a new medical device called Chloe SED® that can be used to support the provision of paracervical blocks. Chloe SED®, priced at US$ 1.5 per device when produced in polypropylene, US$ 10 in polyetheretherketone, and US$ 15 in aluminium, is attached to any 10-cc syringe in low-resource settings to provide paracervical blocks. The device is designed for durability, repairability, maintainability, upgradeability, and recyclability to address environmental sustainability issues in the healthcare domain. Achieving the design of Chloe SED® from a context-specific and circular economy approach revealed correlations between the material choice to manufacture the device, the device's initial cost, product durability and reuse cycle, reprocessing method and cost, and environmental impact. These correlations can be seen as interconnected conflicting or divergent trade-offs that need to be continually assessed to deliver a medical device that provides healthcare for all with limited environmental impact. The study findings are intended to be seen as efforts to make available medical devices to support women's access to reproductive health services.